Isolation and characterization of indigenous microorganisms from agricultural soil / Mahsa Ansari - Ansari, Mahsa (2013)
Microorganisms have many properties include the ability to degrade waste products. In this study Haemolysis was used as an initial selection criterion for the primary isolation of surfactant-producing bacteria. Only β and γ Haemolytic activity were detected in this study which as the presence of a definite clear zone around a colony. From this study, Out of 139 (49 %) hemolytic colonies were observed in this study had shown strong haemolytic activity. The Gram stain results had showed: cocci and bacilli shapes. The colony morphology identification had shown rough, smooth and mucoid appearance. 120 of 139 (86%) isolates possessed biocleaner activity with emulsification against crude oil. Susceptibility towards antibiotics of 138 soil bacterial isolates were tested with impregnated discs (Oxoid) by the Kirby-Bauer method. Inhibition zones were assessed on Mueller-Hinton agar and evaluated after 18 and 24 hours of incubation at 37°C. The disc antibiotic result had shown 29 different types of antibiogram patterns. The lysis solution test could be used as a tool for differentiation between gram positive and gram negative bacteria. All isolates are plasmidless and mice virulence test (LD50) had shown no virulence occurred in all colonies tested.